Psychometric properties of the Postpartum Depression Literacy Scale (PoDLiS) among Chinese perinatal women: a cross-sectional study - Weijian Huang; Xiaohan Li; Zijing Wu; Nan Jiang; Xu Zhang (BMC, 2022)
Abstract Background The aim of the present work was to cross-culturally adapt the Postpartum Depression Literacy Scale (PoDLiS) and use a descriptive cross-sectional design to evaluate its psychometric properties in Chinese perinatal women. Methods Brislin's translation theory was applied to translate the PoDLiS, with subsequent cultural adaptation. The reliability and validity of the PoDLiS were determined using a questionnaire in 635 Chinese perinatal women. Results Good internal consistency was found (omega coefficient, 0.894) for the Chinese version of the Postpartum Depression Literacy Scale (PoDLiS-C), with omega coefficients of the six dimensions of 0.865, 0.870, 0.838, 0.777, 0.837 and 0.794, and a test-retest reliability coefficient of 0.874. The item-level content validity index (CVI) ranged from 0.8 to 1 while the scale-level CVI was 0.968. Moreover, confirmatory factor analysis (CFA) determined satisfactory construct validity of the PoDLiS-C, with the six-factor model explaining 60.76% of the total variance, demonstrating good model fit (likelihood ratio χ2/df, 1.003; goodness-of-fit index, 0.916; adjusted goodness-of-fit index, 0.901; comparative fit index, 0.999; incremental fit index, 0.999; root mean square error of approximation, 0.003; and standardized root mean square error of approximation, 0.0478). Conclusions The PoDLiS-C has adequate psychometric properties. This tool could be used to assess the postpartum depression literacy of perinatal women in Chinese-speaking populations.